PENGEMBANGAN MEDIA PEMBELAJARAN TEMA INDAHNYA KEBERSAMAAN UNTUK MEMBANGUN KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Galuh Rahayuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The aim of the reseach is to develop learning media that of comic to build students’ scientific literacy in the elementary school.This research is development reseach from Bargh and Gall which includes 10 stages. Subjects in this study are media expert,subject expert, and linguitic expert, elementary school teache, and student elementary school. The result of this reseach is learning media in the form of comics that we call this with KOMIK ETLI (ETNOSAINS LITERASI) tema indahnya kebersamaan untuk kelas IV Sekolah Dasar